Germany and the Second World War, Volume 5 : Organization and Mobilization of the German Sphere of Power. Part I. Wartime Administration, Economy, and Manpower Resources, 1939-1941. - Kroener, Bernhard R. (Germany & Second World War., 2000)
This is part one of the fifth volume in the comprehensive and authoritative series, Germany in the Second World War. It deals with developments in wartime administration, economy, and manpower resources in Germany and its occupied territories from 1939-1941. Series description This is the fifth in the magisterial ten-volume Germany and the Second World War. The six volumes so far published in German take the story to 1943, and have achieved international acclaim as a major contribution to historical study. Under the auspices of the Milit--auml--;rgeschichtliches Forschungsamt [Research Institu.